Adenosine and P1 receptors: Key targets in the regulation of sleep, torpor, and hibernation - Ma, Wei-Xiang; Yuan, Ping-Chuan; Zhang, Hui; Kong, Ling-Xi; Lazarus, Michael; Qu, Wei-Min; Wang, Yi-Qun; Huang, Zhi-Li (Frontiers in Pharmacology, 2023)
Sleep, torpor, and hibernation are three distinct hypometabolic states. However, they have some similar physiological features, such as decreased core body temperature and slowing heart rate. In addition, the accumulation of adenosine seems to be a common feature before entry into the three states, suggesting that adenosine and its receptors, also known as P1 receptors, may mediate the initiation and maintenance of these states. This review, therefore, summarizes the current researches on the role of adenosine and P1 receptors in sleep, torpor, and hibernation and also involves the possible neurobiological mechanisms. Understanding these aspects will give us better prospects in sleep disorders, therapeutic hypothermia, and aerospace medicine.